1992
DOI: 10.1093/oxfordjournals.bmb.a072553
|View full text |Cite
|
Sign up to set email alerts
|

HRT: Developments in therapy

Abstract: Various forms of oestrogen have been available for use as Hormone Replacement Therapy (HRT) for approximately 50 years. However, there has been little change in the mode of administration until the last 10-15 years. Although the oral route has remained the mainstay of therapy, non-oral routes of administration have been developed. During the 1970s it became clear that use of unopposed oestrogens in women with an intact uterus resulted in an increase in risk of endometrial carcinoma and thus the current practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Our results show that these are becoming increasingly favoured by physicians in the UK, over those containing CEEs, which are structurally less similar to the oestrogens produced by the human ovary. 27 Our study also demonstrates the differences between the UK and the US in the progestogens prescribed in combined HRT. In our study, only 4.3% of the prescriptions for combined HRT preparations contained MPA as the progestogen while in the US, MPA is by far the most frequently prescribed progestogen in combined HRT.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Our results show that these are becoming increasingly favoured by physicians in the UK, over those containing CEEs, which are structurally less similar to the oestrogens produced by the human ovary. 27 Our study also demonstrates the differences between the UK and the US in the progestogens prescribed in combined HRT. In our study, only 4.3% of the prescriptions for combined HRT preparations contained MPA as the progestogen while in the US, MPA is by far the most frequently prescribed progestogen in combined HRT.…”
Section: Discussionmentioning
confidence: 56%
“…Oestradiol is an endogenous female oestrogen, which is currently a component of several HRT preparations. Our results show that these are becoming increasingly favoured by physicians in the UK, over those containing CEEs, which are structurally less similar to the oestrogens produced by the human ovary 27 . Our study also demonstrates the differences between the UK and the US in the progestogens prescribed in combined HRT.…”
Section: Discussionmentioning
confidence: 61%
“…TX-001HR is the first oral formulation that combines bioidentical E2 and P4 in a single softgel capsule being evaluated for the treatment of moderate to severe VMS in postmenopausal women with a uterus. Combining both E2 and P4 in a single capsule may facilitate compliance and convenience to the patient, 30 but may also increase efficacy and safety while reducing the incidence of withdrawal bleeding. 15,31,32 Additionally, various studies have suggested that bioidentical P4 may have a better side effect profile than synthetic progestogens regarding breast cancer 33,34 and venous thromboembolism.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited data on its long-term effects. 77 Use of the OCP until the menopause: In the UK the upper age limit for prescription of the combined OCP is 45 years. In America, an expert committee have advised the Food and Drugs Administration (FDA) to remove this upper age limit for healthy, non smoking women."…”
Section: New Developmentsmentioning
confidence: 99%